A novel plasmid–Escherichia coli system produces large batch dsRNAs for insect gene silencing. Issue 7 (2nd March 2020) - Ma, Zhong‐Zheng; Zhou, Hang; Wei, Yan‐Long; Yan, Shuo; Shen, Jie
Abstract: BACKGROUND: RNA interference (RNAi)‐based pest management requires efficient delivery and large‐batch production of double‐stranded (ds)RNA. We previously developed a nanocarrier‐mediated dsRNA delivery system that could penetrate an insect's body and efficiently silence gene expression. However, there is a great need to improve the plasmid– Escherichia coli system for the mass production of dsRNA. Here, for efficient dsRNA production, we removed the rnc gene encoding endoribonuclease RNase III in E. coli BL21(DE3) and matched with the RNAi expression vector containing a single T7 promoter. RESULTS: The novel pET28‐BL21(DE3) RNase III‐system was successfully constructed to express vestigial ( vg )‐dsRNA against Harmonia axyridis . dsRNA was extracted and purified from cell cultures in four E. coil systems, and the yields of dsRNA in pET28‐BL21(DE3) RNase III‐, pET28‐HT115(DE3), L4440‐BL21(DE3) RNase III‐ and L4440‐HT115(DE3) were 4.23, 2.75, 0.88 and 1.30 μg mL −1 respectively. The dsRNA expression efficiency of our novel E. coil system was three times that of L4440‐HT115(DE3), a widely used dsRNA production system. The RNAi efficiency of dsRNA produced by our system and by biochemical synthesis was comparable when injected into Harmonia axyridis . CONCLUSION: Our system expressed dsRNA more efficiently than the widely used L4440‐HT115(DE3) system, and the produced dsRNA showed a high gene‐silencing effect. Notably, our pET28‐BL21(DE3) RNase III‐system provides a novel method for the mass production of dsRNA at low cost and high efficiency, which may promote gene function analysis and RNAi‐based pest management. © 2020 Society of Chemical Industry Abstract : The Scarless Cas9 Assisted Recombineering (no‐SCAR) system was applied to achieve scarless deletion of rnc gene in Escherichia coli BL21(DE3). The novel pET28‐BL21(DE3) RNase III– E. coli expressing system was established by transforming with the plasmid pET28‐vestigial ( vg ). The double‐stranded (ds)RNA expression efficiency was about three times that of L4440‐HT115(DE3), a widely used dsRNA production system. The RNA interference (RNAi) efficiency of dsRNA produced by the novel E. coli system and by chemically synthesis is comparable when injecting into Harmonia axyridis .